Association between the evaluation by a patient care team and compliance with the claim of drugs in pharmacy - Robinson Herrera Marín; Jorge Ivan Estrada Acevedo; Ana Maria Restrepo Jimenez (Farmacia Hospitalaria, 2015)
Context: currently is recognized the achieving challenge a adequate adherence. There are multiple methods to detect whether a patient is non-adherent, including claims history of drugs in pharmacy. This method has been considered adequate. Objective: To determine the association between care by an patient care team (including an pharmacist) and compliance with the claim of medicines in pharmacy. Method: case-control study in patients with asthma, chronic obstructive pulmonary disease or allergic rhinitis, they claimed their medicines in pharmacies between October of 2012 and November 2013 (n = 526) .was defined as a case the patients that during the observation period claimed their drugs in pharmacy >95% of the time (n: 263). For univariate analysis absolute and relative frequencies and summary measures were used. For binary analysis, contingency tables, chi-square tests, t-Student (Mann-Whitney U) and ANOVA (Kruskal-Wallis H). The statistical measure of force used was the odds ratio. Was performed multivariate logistic regression. Results: 78.3% of cases and 47.1% of controls had been treated by an interdisciplinary group (p<0,001), which had an exposure time of 1.75 (interquartile range 0.79 to 2.34) and 0.32 years (interquartile range 0.24 to 1.02) years, respectively (p<0,001). The cases claimed their drugs in pharmacy 2.52 times more than controls (ORajusted 2.52 [1.17 to 5.42]). Conclusions: be attended by an patient care team was associated with greater compliance with the claim of medicines in pharmacy